PENGEMBANGAN MODEL PENDIDIKAN PARIWISATA BERBASIS AGROWISATA PERKEBUNAN KOPI DI KABUPATEN JEMBER - Titin Kartini (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
The purpose of this study is to map a map of agro-tourism area of coffee plantations that deserve to be as the development of tourism education model that local content in Jember and to make education lesson plan based tourism agrotourism coffee plantations in Jember. In this study, The researcher used a qualitative descriptive because data that taken is qualitative data obtained from interviews with the source of data. The results of research in the development of agro-based tourism education model plantations in Jember must be observed by all the support elements. With the development of agro-based tourism education model will be central of interest and jember community based planning and is expected to form a Tourism Awareness Society, becoming Travel business communities in the region, caring for Local Culture, Jember as the City of the World Travel Destinations.